Avaliação do desempenho clínico de próteses dentárias totais fixas implantossuportadas (PDTFIs) : estudo retrospectivo - Bordin, Thaisa Barizan (2017)
The high prevalence of edentulous patients associated to the poor retention of the conventional complete dentures, combined to the high survival rate of dental implants and an increased demand for aesthetic dentistry, resulted in a higher number of fixed restorations provided to the patients. However, as any technique, this one is also not free from failures and these can occur due to problems related to the biomechanics of the implant/prosthesis. These complications may be from biologic or technical origin, the first being related to processes affecting the peri-implant hard and soft tissues, and the second to mechanical damage of the implant, implant components and prostheses. Due to the paucity of clinical studies reporting complications in implant fixed complete denture prostheses (IFCDPs), this thesis aimed to evaluate implants and prostheses survival rates, as well as the main complications observed in patients rehabilitated with IFCDPs after at least one year of follow-up. The secondary goal was to evaluate patient satisfaction. Through the electronic records, based on the inclusion criteria, edentulous patients who were rehabilitated with prostheses supported by at least four rough surface dental implants between January 2000 and December 2015 in the Departent of Postgraduate Prosthodontics at Tufts University School of Dental Medicine (Boston, MA, USA) were selected. A comprehensive multidisciplinary examination composed of medical and dental history, clinical examination involving periodontal and prosthetic examination, radiographic analysis and photographs was performed. Comparison was made as well between porcelain IFCDPs (Group 1) and metalresin IFCDPs (Group 2). A questionnaire to assess patient satisfaction regarding the treatment in general, aesthetics, chewing ability, taste, and speaking ability was also applied. For data analysis, Kaplan-Meier estimation curves were used to predict the survival of implants and prostheses. The chi-square test and Fisher's exact test where appropriate and logistic regression analysis were performed. Four hundred fifty-seven implants (Nobel Biocare, Biomet 3i, Straumann) supporting a total of 71 PDTFIs in 52 patients (mean age 65.5 years) were evaluated, with a mean follow-up time of 5.2 years (range 1 to 12 years). Of these prostheses, 38 were in the maxilla and 33 in the mandible (19 edentulous maxillae, 14 edentulous mandibles, 19 both arches); 55 were made of porcelain (porcelain-fused-to-metal or metal-free) (Group 1) and 16 were metal-resin (MR) (Group 2); 36 were cement retained and 35 were retained by screws. Only 6 implants had to be removed, resulting in a survival rate of 98.7%. Of the 71 prostheses, 6 failed (1 porcelain and 5 MR), presenting a survival rate of 91.5%. A total of 274 biologic complications were recorded in 63 prostheses (47 porcelain and 16 MR), being soft tissue recession around the implants (7.7%) the most frequently observed, followed by soft tissue inflammation underneath the prostheses (7.4%), and peri-implant mucositis (6.3%). Soft tissue recession was the most frequent complication in both groups, and no statistical significant difference was observed for any biologic complication between Group 1 and Group 2. A total of 274 technical complications were observed in 57 prostheses (42 porcelain and 15 MR). Wear of the prosthetic material (9.8%) was the most frequent, followed by decementation of the cement-retained IFCDPs (2.9%), and loss of screw access filing material of the screw-retained IFCDPs (2.7%). The rate of wear of prosthetic material was 7.3% for porcelain IFCDPs (Group 1) and 19.4% for metal-resin IFCDPs (Group 2), yielding a statistically significant difference between the two groups (p < 0.05). Regarding the patient satisfaction evaluation, the greatest dissatisfaction was in relation to the ability to chew (12%). However, in general, 94% of the patients were satisfied with the treatment rendered. With a mean exposure time of 5.2 years, high implants and prosthetic survival rates can be expected in rehabilitations with implanted-fixed complete denture prostheses, presence of biologic and technical complications, and a high level of patient satisfaction.